Food and the City. From foodification to delivery - Giannitrapani, Alice (E|C, 2021)
Many historical centres of our cities have been turned into gastronomic villages en plein air. The food outlets have multiplied and the traditional restaurant has exploded, giving life to a myriad of formats. These formats are increasingly linked to the relaunch offered by Instagram pages, to the apps that manage reservations, to the reviews sites. Linking themselves to the possibilities offered by the web, restaurants have transformed their relationship with the city, the practices of food consumption and the rituals of everyday life. We propose to explore this set of processes, starting from the traditional restaurant, and then moving on to the different forms of food consumption that we can experience in our cities today. These forms are often hybrid, coexist in the streets we pass in every day and are inextricably linked to the so called new technologies.